PENGEMBANGAN KARAKTER GURU DALAM MENGHADAPI DEMORALISASI SISWA PERSPEKTIF TEORI DRAMATURGI - Abd Hamid Wahid; Chusnul Muali; Kholifatur Rafikah Qodratillah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
This research means that teachers should help to prevent the decline of teenager’s characters, if we see from the increasing sophisticated era, education character is often eroded gradually. The teacher’s strategy to instill the character of student by interpolating the values of human behavior associated with God Almighty and humanity. The Division: (1) The hearts consisting of: Religious, honest, responsible, social care and environment care, (2) The thinking consists of: intelligent, creative, likes to read and curiosity, (3) The Body consists of: keep health of the body and the environment, (4) Exercise and initiative consists of: Caring and helping. From several of behavioral the teenager delinquency rate will decrease. Synchronized with the theory of dramaturgy, teacher is becoming an actor in the front stage area as a driving force and guide who not only transfers science but also character educators to be good generations of the nation. From back stage, teacher role as friends to be well received by students and exemplary.